Comparative Study for Multiple Coordinated Views Across Immersive and Non-immersive Visualization Systems - Su, Simon; Perry, Vincent; Dasari, Venkateswara (Virtual, Augmented and Mixed Reality. Multimodal Interaction, 2019)
Our objective is to qualitatively assess how users interact with and explore heterogeneous views of data in novel hybrid 2D and 3D visual analytic applications, and assess attitudinal responses on the usefulness of such applications. The application used for the study visualizes simulated network communication data of multiple assets over time, and shows topological, geospatial, and temporal aspects of the data in multiple views. We first perform a usability test, where the participants complete a couple of exploratory tasks: one, identifying corresponding assets in a visualization, and two, identifying patterns/relationships between particular assets. Participants perform the same tasks using several different system configurations: using only 2D visualizations, using 2D and 3D visualizations together but as separate applications, and using the 2D and 3D visualizations together with multiple coordinated views across the two systems. Afterwards, participants complete a user survey of questions that probe at user preferences and opinions about the relative effectiveness of each system towards accomplishing the given tasks. We discuss how the results of the study confirm current system design decisions, and also evaluate additional user-centric characteristics that must be considered to inform future design decisions. These results will inform hypotheses and guidelines for a future behavioral, quantitative study.